Pengembangan E-Comic Problem-Based Learning Materi Perubahan Lingkungan untuk Memberdayakan Literasi Digital dan Keterampilan Pemecahan Masalah Siswa Kelas X - Firdha Ismifatichah; Mimien Henie Irawati; Herawati Susilo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop a Problem-Based Learning based E-comic learning media on environmental change material for Grade X Phase E students that is valid and practical. The method used in this study is Research and Development (R&D) using the Lee & Owens model which consists of five stages: assessment/analysis, design, development, implementation, and evaluation. Data were collected through structured interviews, questionnaires, expert validation, and field trials involving students. The results of the study indicate that the developed Problem-Based Learning based E-comic learning media received very valid assessments from material experts, media and teaching material experts, as well as biology education practitioners. In addition, the field trial results show that the developed learning media has a very high level of practicality for use in the learning process. Inconclusion, the developed Problem-Based Learning based E-comic learning media on environmental change material is feasible to be used as a learning media to support the biology learning process for Grade X Phase E students. Keywords: E-Comic, Environmental Change, Learning Media, Problem-Based Learning